2016
DOI: 10.1039/c6cp01066k
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory study of oxygen reduction reaction on Pt/Pd3Al(111) alloy electrocatalyst

Abstract: Developing efficient catalysts for the oxygen reduction reaction (ORR) to reduce cathode Pt loading without sacrificing the performance has been under intensive research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(38 citation statements)
references
References 56 publications
4
34
0
Order By: Relevance
“…Besides the reactant, the corresponding E ads of ORR intermediates are 4.08, 3.57, and 1.17 eV for OOH, O, and OH, respectively. In comparison with the Pt(111) (3.55 eV for OOH, 1.38 eV for O, and 0.64 eV for OH) (Xiao et al, 2016 ), the obviously weak adsorption ability of the center Ni atom has been observed.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the reactant, the corresponding E ads of ORR intermediates are 4.08, 3.57, and 1.17 eV for OOH, O, and OH, respectively. In comparison with the Pt(111) (3.55 eV for OOH, 1.38 eV for O, and 0.64 eV for OH) (Xiao et al, 2016 ), the obviously weak adsorption ability of the center Ni atom has been observed.…”
Section: Resultsmentioning
confidence: 99%
“…The E a would help as the selection criteria between O 2 dissociation and OOH formation. 41 As shown in Table 3, O 2 dissociation exhibited much higher activation energy (1 eV) than that of OOH formation (0.36 eV). Therefore, OOH formation is the preferred initial step for ORR.…”
Section: Orr Mechanisms On the Pt-skin Pt 3 V(111) Surfacementioning
confidence: 91%
“…There are three possible ORR mechanisms. These are O 2 dissociation mechanism, OOH dissociation mechanism, and 16,41,63,64 as shown in Fig. 4.…”
Section: Activation and Reaction Energy Of Orr Elementary Stepsmentioning
confidence: 99%
“…It can be practically applied in many fields, such as mobile power, aerospace, submarines, and so on; and has a broad application prospect [3,4]. In the past decades, many novel materials [5][6][7][8][9] and fuel cell unit types [10,11] have been proposed and developed due to the contributions of a large number of scientists and funding support. Generally, the current art of the fuel cell unit manufacture technology and performance can well satisfy the commercialization requirements [12][13][14].…”
Section: Introductionmentioning
confidence: 99%